2010
DOI: 10.3109/10428194.2010.505820
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations ofp15INK4Bandp16INK4Agenes in pediatric primary myelodysplastic syndrome

Abstract: We studied the methylation status of the p15(INK4B) and p16(INK4A) genes in 47 pediatric patients with primary MDS, its correlation with subtype, and the role of p15(INK4B) and p16(INK4A) in the evolution of MDS toward AML. Aberrant methylation of the p15(INK4B) gene was detected in 15 of 47 patients (32%), whereas only four patients demonstrated methylation of the p16(INK4A) gene (8%). The frequency of p15(INK4B) methylation was significantly higher in RAEB and RAEB-t subtypes (p<0.003). Aberrant methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…However, more recently, it was found that even in patients with the RARS subtype, which falls within the lower risk of MDS, p15INK4b was found to be the most frequently methylated gene (>20% of cases) of 25 known tumor suppressors that were evaluated in the study (Valencia et al, 2011). Although most studies have been conducted in MDS in adults, comparable levels of aberrant methylation patterns have been observed in pediatric MDS patients as well (Hasegawa et al, 2005), and a similar correlation with the disease subtypes has been established (Rodrigues et al, 2010). In chronic myelomonocytic leukemia (CMML), aberrant methylation of p15INK4b is found in about 60% of cases and is associated with a high proportion of blastic transformation (Tessema et al, 2003).…”
Section: Introductionmentioning
confidence: 70%
“…However, more recently, it was found that even in patients with the RARS subtype, which falls within the lower risk of MDS, p15INK4b was found to be the most frequently methylated gene (>20% of cases) of 25 known tumor suppressors that were evaluated in the study (Valencia et al, 2011). Although most studies have been conducted in MDS in adults, comparable levels of aberrant methylation patterns have been observed in pediatric MDS patients as well (Hasegawa et al, 2005), and a similar correlation with the disease subtypes has been established (Rodrigues et al, 2010). In chronic myelomonocytic leukemia (CMML), aberrant methylation of p15INK4b is found in about 60% of cases and is associated with a high proportion of blastic transformation (Tessema et al, 2003).…”
Section: Introductionmentioning
confidence: 70%
“…It has been observed the importance of epigenetic alterations in the pathogenesis of MDS, but the majority of these studies is focused in adult patients. Few studies showed the epigenetic alterations in children (Hasegawa et al, 2005;Rodrigues et al, 2010;Vidal et al, 2007). Rodrigues and colleagues, 2010, suggested that methylation of p15 INK4B and p16 INK4A genes are epigenetic alterations in pediatric MDS patients and, as in adult patients, are later events associated with the leukemogenesis process in MDS.…”
Section: Pediatric and Adult Myelodysplastic Syndromementioning
confidence: 99%
“…In fact, it is a correction factor, which is necessary w h e n w e h a v e a s m a l l n u m b e r o f d a t a . T h i s is known as chi-square with continuity Quantitative analysis to evaluate whether there was a correlation between percentage of p15 INK4B methylation and MDS subtypes was performed in (Rodrigues et al, 2010). The percentage of p15 INK4B methylation was higher in RAEB and RAEB-t compared to RC.…”
Section: Responsementioning
confidence: 99%
See 2 more Smart Citations